Checklist of the ichthyofauna of the Rio Negro basin in the Brazilian Amazon - Hélio Beltrão; Jansen Zuanon; Efrem Ferreira (ZooKeys, 2019)
This study presents an extensive review of published and unpublished occurrence records of fish species in the Rio Negro drainage system within the Brazilian territory. The data was gathered from two main sources: 1) litterature compilations of species occurrence records, including original descriptions and revisionary studies; and 2) specimens verification at the INPA fish collection. The results reveal a rich and diversified ichthyofauna, with 1,165 species distributed in 17 orders (+ two incertae sedis), 56 families, and 389 genera. A large portion of the fish fauna (54.3% of the species) is composed of small-sized fishes < 10 cm in standard length. The main groups are Characiformes (454 species; 39.0%), Siluriformes (416; 35.7%), Gymnotiformes (105; 9.0%), and Cichliformes (102; 8.8%). The species composition differs between the main aquatic environments, such as: main channel (159 species), lakes (296), tributary rivers (596), small streams (234), seasonal beaches (186), and rapids (41). Part of the ichthyofauna is shared with adjacent basins, such as the Orinoco, rivers of the Guiana Shield, lower Solimões/Amazonas and upper Amazonas, which contributes to the remarkable ichthyofaunal diversity of the basin. A high rate of species endemism was observed in Characidae (24), Loricariidae (18), Cichlidae (18) and Callichthyidae (18), totalling 156 species (13.4%) endemic to the basin. An estimation of the species richness for the Rio Negro basin, considering 23 published references, resulted in 1,466 and 1,759 species (Jackknife 1 and 2, respectively), which seems reasonable when considering the large number of morphotypes left out of the present list and the low sampling effort in many areas of the basin. The results presented herein provide an additional tool for environmental managers and decision makers for conservation purposes of one of the richest and most well-preserved sub-basins of the Rio Amazonas system.